NT-proBNP level in stage 3-4 chronic kidney disease and mortality in long-term follow-up: HAPPY study subgroup analysis - MUTLU, BÜLENT (TURKISH SOC CARDIOLOGY, 2020)
Objective: This was an investigation of the relationship between the N-terminal pro-brain natriuretic peptide (NT-proBNP) level and mortality in patients with stage 3-4 chronic kidney disease (CKD). Methods: This study was designed as a subgroup analysis of the Heart Failure Prevalence and Predictors in Turkey (HAPPY) study. The HAPPY study included 4650 randomly selected individuals from the 7 geographical regions of Turkey. A total of 191 subjects from the original cohort with an estimated glomerular filtration rate (eGFR) <60 mL/min/1.1.73 m(2) were enrolled in this study and the relationship between NT-proBNP and mortality was investigated. Prognostic variables for total and cardiovascular mortality were also examined using Cox regression analysis. Results: The mean length of follow-up was 76.12 +/- 22.45 months. The mean NT-proBNP level was 423.54 +/- 955.88 pg/mL. During follow-up, 51 subjects (26.7%) died from any cause and 36 subjects (18.8%) died from a cardiovascular cause. The presence of hypertension (hazard ratio [HR]: 1.89; 95% confidence interval [CI]: 1.01-3.50; p=0.048), anemia (HR: 2.49; 95% CI: 1.20-5.15; p=0.014), male gender (HR: 2.64; 95% CI: 1.44-4.86; p=0.002) and log NT-proBNP (HR: 4.93; 95% CI: 2.83-8.58; p<0.001) were independent variables for total mortality. The presence of hypertension (HR: 2.47; 95% CI: 1.09-5.56; p=0.029), male gender (HR: 2.79; 95% CI: 1.38-5.62; p=0.004), eGFR (HR: 0.94; 95% CI: 0.91-0.98; p=0.005) and log NT-proBNP (HR: 6.31; 95% CI: 3.11-12.81; p<0.001) were independent predictors of cardiovascular mortality. Conclusion: NT-proBNP was found to be an independent prognostic marker in patients with stage 3-4 CKD.
Keywords: Chronic kidney disease; mortality; N-terminal pro-brain natriuretic peptide; CARDIOVASCULAR EVENTS; NATRIURETIC PEPTIDE; ALL-CAUSE; DEATH